Keberkesanan pengurusan Kementerian Kebudayaan, Kesenian dan Warisan Malaysia dalam memartabatkan kempen budi bahasa dalam kalangan remaja Kajian kes Jabatan Kebudayaan, Kesenian dan Warisan Negeri Sarawak - Lah, L.L (Universiti Malaysia Sarawak, (UNIMAS), 2006)
This reseach is conducted to study the role of Kementerian Kebudayaan, Kesenian dan Warisan (KeKKWa) in the Campaign of Budi Bahasa among the teenagers. In this research, the researcher pointed out the effectives of KeKKWa management from the activities and programmes that they had held. This also examines the respond and acceptance of new generation especially teeneger toward this campaign.